Economic Burden and Management of Systemic Sclerosis-Associated Interstitial Lung Disease in 8 European Countries: The BUILDup Delphi Consensus Study - Davidsen JR; Miedema J; Wuyts W; Kilpeläinen M; Papiris S; Manali E; Cordeiro CR; Morais A; Perez M; Asijee G; Cendoya D; Soulard S (Springer, 2022)
Introduction Systemic sclerosis (SSc) is a rare chronic autoimmune disease characterised by microvascular damage, immune dysregulation and fibrosis, affecting the skin, joints and internal organs. Interstitial lung disease (ILD) is frequently associated with systemic sclerosis (SSc-ILD), leading to a poor prognosis and a high mortality rate. The aim of the BUILDup study (BUrden of Interstitial Lung Disease Consensus Panel) was to investigate the overall disease management and to estimate the social and economic burden of SSc-ILD across 8 European countries. Methods A modified Delphi method was used to obtain information on the management of SSc-ILD patients among 40 specialists (panellists) from 8 European countries. Average annual costs per patient and country were estimated by means of a direct cost-analysis study. Results The panellists had managed 805 SSc-ILD patients in the last year, 39.1% with limited (L-SSc-ILD) and 60.9% with extensive (E-SSc-ILD) disease. Of these, 32.8% of the panellists started treatment at diagnosis, 42.3% after signs of deterioration/progression and 24.7% when the disease had become extensive. The average annual cost of SSc-ILD per patient ranged from euro6191 in Greece to euro25,354 in Sweden. Main cost drivers were follow-up procedures, accounting for 80% of the total annual costs. Hospitalisations were the most important cost driver of follow-up costs. Healthcare resource use was more important for E-SSc-ILD compared to L-SSc-ILD. Early retirement was taken by 40.4% of the patients with an average of 11.9 years before the statutory retirement age. Conclusions SSc-ILD entails not only a clinical but also a social and economic burden, and is higher for E-SSc-ILD.